Pre-Columbian Rock Mulching as a Strategy for Modern Agave Cultivation in Arid Marginal Lands - Ortiz-Cano, Hector; Hernandez-Herrera, Jose Antonio; Hansen, Neil C.; Petersen, Steven L.; Searcy, Michael T.; Mata-Gonzalez, Ricardo; Cervantes-Mendívil, Teodoro; Villanueva-Morales, Antonio; Park, Pil Man; Stewart, J. Ryan (Frontiers in Agronomy, 2020)
Cultivation of C3 and C4 crops in semi-arid regions will be severely constrained as global temperatures rise. Consequently, alternative crops need to be sought out that adapt well to heat and drought and are productive despite limited access to water. Traits, such as crassulacean acid metabolism (CAM), enable economically important species such as those in the Agave genus adapt to drought and high temperatures. The succulence and high efficiency of agaves, which enables them to produce biomass with little water, underscores their feasibility as an alternative crop for semi-arid regions, such as the Sonoran Desert in the southwestern U.S. In this paper, we offer a review of the suitability for cultivation of agaves via dryland farming, particularly by rock mulching techniques used by pre-Columbian, Sonoran Desert farmers. This analysis dovetails with information also provided on the biological traits of Agave and its historical and present utilization. Pre-Columbian, Hohokam dryland farmers used rock mulching in the form of rock piles to cultivate agaves. Rock piles acted as a type of mulch to harvest rainfall and to retain soil moisture, which allowed the Hohokam to intensively cultivate agaves during multi-year droughts. Remains of Hohokam rock mulching for agave production can be found at archaeological sites in central Arizona, which provides evidence of the utility of dryland farming and ancient agricultural innovation to reconcile water scarcity in the region. Moreover, the use of rock piles likely bolstered Agave productivity in marginal lands. Although little is known of historic rock mulching to cultivate agaves and its biological implications on plant productivity we suggest its application as a dryland farming model could be a sustainable strategy in the U.S. Southwest.